Arbitration clause for an arbitral tribunal in Poland based on Art. 33 CMR Convention - Adamus, Rafał (The Opole Studies in Administration and Law, 2020)
In matters that are subject to the CMR Convention, under the rule of Art. 33 of this Convention, the arbitration court is obliged, first, to apply the CMR Convention and it is not permissible to apply, in place of the scope of the CMR Convention, another legal order or extra-legal principles. Secondly, as far as it results from the CMR Convention, the arbitration court should apply the applicable national law. Thirdly, the arbitration court settles the dispute according to the law applicable to a given relationship, and when the parties have expressly authorized it – in compliance with general principles of law or principles of equity. Fourthly, the arbitral tribunal takes into consideration the provisions of the contract and the established habits applicable to the given legal relationship. The arbitration agreement regarding the dispute subject to the CMR Convention will therefore be of a complex nature due to the requirement of Art. 33 of the CMR Convention as to the indication that a uniform law applies in arbitration proceedings – the subject of inter-city agreement. The parties should indicate the following in the content of the arbitration clause: 1) obligatory CMR convention, as required by Art. 33 CMR Convention 2) optional national law to which the CMR Convention refers, and in the absence of such an indication, the arbitration court will apply the law applicable to a given legal relationship, and possibly another national law to which the CMR Convention does not refer, although such a solution would be a source of many complications or general legal principles or rules of equity. For practical reasons, it is worth taking into account other issues, such as the language of the proceedings, in the arbitration clause.